2022
DOI: 10.3390/vaccines10020278
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perception towards COVID-19 Vaccination among the Adult Population: A Cross-Sectional Study in Turkey

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic continues to wreak havoc on lives and ravage the world. Several vaccines have been approved for use against COVID-19; however, there may be hesitancy and negative perceptions towards vaccination, which may reduce the willingness to be vaccinated. Further, studies assessing the current perception toward COVID-19 vaccination are scarce. This study aimed to assess community knowledge, attitudes, and perceptions regarding COVID-19 vaccines among the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
5
24
1
Order By: Relevance
“…Our findings have confirmed previous findings suggesting those from lower socioeconomic communities, described as lower family wealth, poorer educational achievement, unemployment, and declining wages due to the pandemic, have been found to have higher rates refusal to accept vaccination. This may be because people in these communities and groups of people do not trust public sector officials or the government [ 32 , 33 ]. Furthermore, people who are single and/or lived alone had much higher vaccination acceptance rates than those who lived with others (partners, family members, friends, or housemates).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have confirmed previous findings suggesting those from lower socioeconomic communities, described as lower family wealth, poorer educational achievement, unemployment, and declining wages due to the pandemic, have been found to have higher rates refusal to accept vaccination. This may be because people in these communities and groups of people do not trust public sector officials or the government [ 32 , 33 ]. Furthermore, people who are single and/or lived alone had much higher vaccination acceptance rates than those who lived with others (partners, family members, friends, or housemates).…”
Section: Discussionmentioning
confidence: 99%
“…People who were constantly informed by specialized medical staff had a statistically significant higher vaccination rate, while people who chose to get information from friends, family, and co-workers had the strongest unwillingness toward getting vaccinated. Furthermore, previous research has indicated that recommendations from health officials as the first source of information about the COVID-19 pandemic are statistically associated with a high degree of confidence in immunization [ 32 ]. Consequently, high levels of vaccination acceptance require trust in science and medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a difference in the level of knowledge of the three occupational categories, with physicians having the highest rates and nursing assistants having the lowest, all participants with adequate knowledge of both virus and vaccination subjects, were shown to have the intention to get vaccinated at a higher rate, which has been confirmed by other studies. 40 , 66 …”
Section: Discussionmentioning
confidence: 99%
“…Among nurses, stronger COVID-19 vaccination intention was attributed to greater vaccine confidence, younger age and a stronger sense of collective responsibility [7]. In the Turkish general population, age was negatively related to vaccination behaviour, while education and past experiences with other vaccines or with COVID-19 had positive association with intention [11]. Further, other aspects, such as vaccine safety, protecting others and the seriousness of the disease, were also linked with greater willingness to be vaccinated [12].…”
Section: Introduction-covid-19: Vaccination Intentions and Vaccine He...mentioning
confidence: 96%